2010
DOI: 10.1007/s11548-010-0521-9
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular orientation variability and symmetry based on CT scans of adults

Abstract: A new method of computing patient-specific abduction and anteversion angles from a CT study of the anterior pelvic plane and the left and right acetabular rim planes was reliable and accurate. We found that the acetabular rim plane can be reliably and accurately computed from identified points on the rim. The novelty of this work is that angular measurements are performed between planes on a 3-D model rather than lines on 2-D projections, as was done in the past.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Our average healthy parameter values were within a standard deviation of that from previous studies: pelvic (Baudoin et al, 2008;Chaibi et al, 2012;Okuda et al, 2007;Strecker et al, 1997;Yoshimoto et al, 2005), acetabular (Fowkes et al, 2011;Lubovsky et al, 2010Lubovsky et al, , 2012Tohtz et al, 2010), and femoral: (Cooke et al, 1991;Moreland et al, 1987;Than et al, 2012).…”
Section: Increase In Femoral Mechanical Angle (Fma)supporting
confidence: 82%
“…Our average healthy parameter values were within a standard deviation of that from previous studies: pelvic (Baudoin et al, 2008;Chaibi et al, 2012;Okuda et al, 2007;Strecker et al, 1997;Yoshimoto et al, 2005), acetabular (Fowkes et al, 2011;Lubovsky et al, 2010Lubovsky et al, , 2012Tohtz et al, 2010), and femoral: (Cooke et al, 1991;Moreland et al, 1987;Than et al, 2012).…”
Section: Increase In Femoral Mechanical Angle (Fma)supporting
confidence: 82%
“…Some of the criticisms pertaining to previous threedimensional studies have involved loss of accuracy due to surface modification such as aggressive smoothing and surface simplification through mesh size reduction 6,7,10,27,28,32 . The highresolution scans and improved capabilities of commercially available rendering software used in the present study allowed us to address these deficiencies, permitting smoothing algorithms with negligible change in volume for the models (<0.1%).…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have fit a plane to the acetabulum, providing true three-dimensional measures of orientation while controlling for pelvic positioning. Several studies have performed direct measurements on anatomic or cadaveric specimens 5,8,23 , and others have leveraged the benefits of computer-generated renderings 6,11,[27][28][29] . Interestingly, these studies have suggested that females have acetabula that are more anteverted than males.…”
mentioning
confidence: 99%
“…A second method that involves selecting anatomical landmarks for APP manually has inconsistencies because the ASIS and pubic tubercle are ambiguous anatomical structures that are difficult to represent with specific points. Furthermore, manual selection of landmark points on CT images is tedious, time-consuming and error-prone [11]. A third method utilizes the SB plane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they did not compare their results to those obtained by a highly experienced surgeon. Lobovsky et al [11] manually selected landmarks to derive the APP. This method is commonly applied but is tedious and time-consuming.…”
Section: Introductionmentioning
confidence: 99%